2022
DOI: 10.3390/cimb44020060
|View full text |Cite
|
Sign up to set email alerts
|

Curtobacterium spp. and Curtobacterium flaccumfaciens: Phylogeny, Genomics-Based Taxonomy, Pathogenicity, and Diagnostics

Abstract: The genus of Curtobacterium, belonging to the Microbacteriaceae family of the Actinomycetales order, includes economically significant pathogenic bacteria of soybeans and other agricultural crops. Thorough phylogenetic and full-genome analysis using the latest genomic data has demonstrated a complex and contradictory taxonomic picture within the group of organisms classified as the Curtobacterium species. Based on these data, it is possible to delineate about 50 new species and to reclassify a substantial part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 116 publications
(159 reference statements)
1
16
0
Order By: Relevance
“…The attribution of novel isolates to Curtobacterium sp. was initially assessed using the genus-specific diagnostic PCR test [ 18 ], as well as using the Cff-specific assay [ 19 ]. For strains of the collection that demonstrated a positive signal in both cases, further study was conducted aimed at assessing the physiological and biochemical properties of the isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The attribution of novel isolates to Curtobacterium sp. was initially assessed using the genus-specific diagnostic PCR test [ 18 ], as well as using the Cff-specific assay [ 19 ]. For strains of the collection that demonstrated a positive signal in both cases, further study was conducted aimed at assessing the physiological and biochemical properties of the isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six strains were classified as C. flaccumfaciens and 28 strains were classified as pathovars of C. flaccumfaciens . Previous research [ 19 ] revealed inconsistencies in the taxonomy of genus Curtobacterium and called for taxonomic re-evaluation. Thus, all 197 genomes have been used for analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic determinants of environmental adaptation and plant pathogenicity among Curtobacterium sp. are not completely understood [ 19 ], and may be influenced by mobile elements such as plasmids as well as prophages or their remnants. Bacteriophages are viruses that infect bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Psg strains reacted positively with PCR assay for gene cfl [ 8 ] and had sequences of gene cts fragments [ 81 ] that were most similar to the corresponding sequence in the genome of the Psg strains in Genbank. Strains Cff were attributed by PCR using genus-specific [ 82 ] and species-specific [ 83 ] primers.…”
Section: Methodsmentioning
confidence: 99%